The Feasibility, Safety, and Efficacy of the Preemptive Indwelling of Double-J Stents in Percutaneous Nephrolithotomy Surgery: A Randomized Controlled Trial - Bai, Fuding; Wu, Huifeng; Zhang, Nan; Chen, JiMin; Wen, Jiaming (Urology Journal, 2020)
Purpose: The goal of this study is to compare the feasibility, safety, and efficacy of the preemptive indwelling of double-J stents (PI-DJS) versus the conventional preemptive indwelling of ureteral catheters (PI-UC) in percutaneous nephrolithotomy (PCNL) via a randomized, controlled clinical study. Materials and methods: A total of 75 patients with complex renal calculi underwent PCNL surgery and were randomized, using random number table, to receive either a PI-DJS (37 cases) or a PI-UC (38 cases). All operations were performed by the same experienced surgeon. Several outcomes were measured, including duration of operation, time to establish passage, level of hemoglobin decline, rate of stone clearance and incidence of complications. Results: Guided by B-ultrasound, percutaneous passages were successfully established in all patients who then underwent one-stage PCNL. The time required to establish a passage using a PI-DJS was 7.5min, whereas that of the group who received a PI-UC was 11.5min (P < 0.01). There was no significant difference between the two groups in terms of operation duration, postoperative Hb decline rate, stone clearance rate, and perioperative complication incidences (all P > 0.05). Conclusion: PI-DJS during PCNL allowed for a reliable and stable reflux from the bladder into the renal pelvis to produce an artificial hydronephrosis without the formation of microbubbles, unlike conventional ureteral catheters.